ACOUSTIC-ELECTRONIC CHEMICAL SENSORS ON THE BASIS OF MODIFIED NANOTUBES ARRAYS: ADSORPTIVE PROPERTIES OF CNT ARRAYS - A. S. Chashynski; V. V. Barkaline (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Perspectives of carbon nanotubes arrays in chemical sensors with acoustic information-carrying signal are discussed. The arrays are regarded as nanostructured disperse medium with intertube molecular interaction modulated by molecules adsorbed in the space among the tubes and changing elastic properties of the array. Adsorptive properties of the arrays are described. The possibility of their non-covalent functional modification is proved. Chemical sensitivity of such systems and ways of its selectivity rising are discussed.